Pengaruh Model Pembelajaran Problem Based Learning Terhadap Kemampuan Menulis Teks Laporan Hasil Observasi Siswa Kelas X SMAN 6 Pandeglang - Mulya Saroh (Jurnal Artikula, 2025)
This study aims to determine the effect of the problem based learning model on the ability to write observation report texts of class X students of SMAN 6 Pandeglang. The method used in this study is a quantitative approach. The population and sample in this study were class X of SMAN 6 Pandeglang. The instrument used in this study was a test of writing skills of observation report texts. The test used was a written test. Based on the results of data analysis, it was concluded that there was a difference in the effect of writing skills of observation report texts between students who studied using the problem based learning model and students who studied using the discovery learning model. The writing skills of observation report texts of students who studied using the problem based learning model were better than students who studied using the discovery learning model. This can be seen from the results of the t-test which showed significant results in improving the writing skills of observation report texts of class X students of SMAN who studied using the problem based learning model.